2023
DOI: 10.3389/feart.2023.1162220
|View full text |Cite
|
Sign up to set email alerts
|

Changes of extreme precipitation in the middle and lower reaches of the Yangtze River and their correlation with atmospheric circulation

Abstract: Under the backdrop of climate change, the rising frequency and intensity of extreme precipitation events in the middle and lower Yangtze River (MLYR) region are causing serious consequences and economic losses. To assess regional risk and understand the impact of atmospheric circulation on extreme precipitation, it's crucial to analyze the spatial and temporal fluctuations of these events, focusing on the time-frequency phase relationship. Using the observed precipitation data from 1979 to 2015, nine extreme p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Besides the monsoon, we have identified that the PDO (r = −0.472, p < 0.01) and SOI (r = 0.459, p < 0.01) are the major factors that significantly influence the variability in daily rainstorm frequency in the HJB. This finding aligns with existing studies in the Yangtze River basin (Wang et al, 2022;Xiao et al, 2015;Yang et al, 2023). Some studies have already highlighted that the ENSO and PDO are two of the most influential climatic phenomena, with dominant impacts on extreme precipitation changes in various regions over the world (Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Besides the monsoon, we have identified that the PDO (r = −0.472, p < 0.01) and SOI (r = 0.459, p < 0.01) are the major factors that significantly influence the variability in daily rainstorm frequency in the HJB. This finding aligns with existing studies in the Yangtze River basin (Wang et al, 2022;Xiao et al, 2015;Yang et al, 2023). Some studies have already highlighted that the ENSO and PDO are two of the most influential climatic phenomena, with dominant impacts on extreme precipitation changes in various regions over the world (Wei et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the monsoons, rainstorm variation is also affected by many other natural factors. Referring to the literature (Kong et al, 2017;Yang et al, 2023), a total of 14 circulation factors that closely affected the rainstorms are selected for correspondence, as shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, monitoring precipitation is critical for understanding its impact on society and for disaster planning and mitigation [1,2]. Climate change has been impacting precipitation regimes, leading to changes in the frequency, duration, and/or intensity of precipitation events [3][4][5][6][7]. Rising planetary temperatures increase the atmosphere's capacity to hold water (≈7% per 1°C), which can result in greater precipitation intensity [8].…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that heavy rainfall days exhibited a decrease before 2013, and the decreasing trend was alleviated after 2013. Given the spatiotemporal variability of mean and extreme precipitation climatology, several studies have analyzed the reasons for the observed differences [21][22][23][24][25], including geographical factors [26][27][28][29], global warming [30][31][32], circulation factors [11,[33][34][35][36], and urbanization [37,38].…”
Section: Introductionmentioning
confidence: 99%